The Theological Profile of the Peshitta of Isaiah - Bodor, Attila, (Supplements to the Textual History of the Bible ;, 2021)
In The Theological Profile of the Peshitta of Isaiah , Attila Bodor explores theological elements in the book of Isaiah as represented in the Peshitta. Through a close study of its interpretative renderings, the author shows that this lesser-known ancient version is not only an important witness to textual history and a repository of early exegetical traditions but also testifies to the beliefs of the early Syriac-speaking community from which the Peshitta emerged. In the monograph, sixty-three Peshitta divergences from the Hebrew version of Isaiah are collected and analyzed in order to illustrate the theological implications and the impact of these divergent renderings on the interpretation and reception of the major Isaianic themes that treat God, the Messiah, and the people of God.